2020
DOI: 10.1093/eurheartj/suaa136
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in ischaemic heart disease: not sleeping enough, not brushing your teeth, and skipping breakfast—three ways of increasing your risk of myocardial infarction?

Abstract: Despite optimal medical therapies, there is currently a persistent residual cardiovascular risk. The most likely pathway responsible for this residual risk has been identified in the inflammatory state. Recent studies have confirmed that inflammation increases cardiovascular risk independently from LDL cholesterol levels. Addressing traditional risk factors, such as obesity, cigarette smoking, diabetes, arterial hypertension, and dyslipidaemia, also provides an important reduction of the levels of inflammation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…The results of the data from this research are that the number of portions is not good for young women at MTSN 1 Deli Serdang. It is known that young women are sometimes lazy about eating breakfast because they are afraid of stomach ache and can come to school late and also don't eat dinner because they are afraid of getting fat (Muscente & de Caterina, 2020;Ochoa et al, 2021). Wrong eating patterns and social influences because you want to have a slim body and strict diets can result in weight loss and the body lacking the nutrients the body needs, such as iron.…”
Section: A Bivariate Analysismentioning
confidence: 99%
“…The results of the data from this research are that the number of portions is not good for young women at MTSN 1 Deli Serdang. It is known that young women are sometimes lazy about eating breakfast because they are afraid of stomach ache and can come to school late and also don't eat dinner because they are afraid of getting fat (Muscente & de Caterina, 2020;Ochoa et al, 2021). Wrong eating patterns and social influences because you want to have a slim body and strict diets can result in weight loss and the body lacking the nutrients the body needs, such as iron.…”
Section: A Bivariate Analysismentioning
confidence: 99%
“…Our primary focus was on promoting engagement with the target behavior—oral self-care practices. Clinical guidelines typically endorse toothbrushing twice daily, in the morning and evening, as the most effective preventive routine [ 13 ]. Thus, the goal was to design messages that serve as a subtle cue for brushing by making oral health salient in the morning and evening.…”
Section: Introductionmentioning
confidence: 99%
“…Current epidemiological studies [ 34 - 45 ] have confirmed that SD is associated with increased incidence of CVDs, such as coronary artery disease, hypertension, arrhythmia, diabetes, and obesity. People who sleep less than six hours a day are at increased risk of coronary heart disease (CHD), compared with those who sleep between six and nine hours a day [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…SD can induce different biological effects, such as changes in autonomic nervous system regulation, increased oxidative stress, changes in inflammatory and coagulation responses, and accelerated atherosclerosis progression [25][26][27][28][29][30][31]. These mechanisms link SD with CVD and metabolic disorders [16,26,[32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%